(untitled) (Revista científica Olimpia, 2019)
The present research work was oriented to the development of a management system based on engineering requirements for the control and management of medical records, the system sought to provide substantial improvements in the management of medical information of each patient, athletes and workers served. The investigative idea arose due to the inconveniences present in the Provincial Center of Sports Medicine (CEPROMEDE), the Sports Schools and the Sports Academies of the province, such as the loss of information and inconsistencies in the medical records. The research was of projective type framed in a comprehensive level, with a mixed source design, applied on the current enrollment of schools, academies and CEPROMEDE. The methodologies used were Requirements Engineering and Extreme Programming, allowing the efficient obtaining of the requirements based on a thorough analysis of the environment under study and the active incorporation of medical personnel as facilitators of the necessary information for the design and construction of the technological solution, in addition the use of the Unified Modeling Language (UML) allowed to graphically represent the solutions, having as final result a first operative version of the system that adjusts to the existing needs.